The aggregate and distributional implications of credit shocks on housing and rental markets - Juan Castellanos; Andrew Hannon; Gonzalo Paz Pardo (European Central Bank (ECB), 2024)
We build a model of the aggregate housing and rental markets in which house prices and rents are determined endogenously. Households can choose their housing tenure status (renters, homeowners, or landlords) and the size of their homes depending on their age, income and wealth. We use our model to study the impact of changes in credit conditions on house prices, rents and household welfare. We analyse the introduction of policies that limited loan-to-value (LTV) and loan-to-income (LTI) ratios of newly originated mortgages in Ireland in 2015 and find that, consistent with empirical evidence, they mitigate house price growth but increase rents. Homeownership rates drop, and young and middle-income households are negatively affected by the reform. An unexpected permanent rise in real interest rates has similar effects - by making mortgages more expensive and alternative investments more attractive for landlords, it increases rents relative to house prices.
Keywords: D15; E21; E30; E51; G51; 330; House Prices; Rental Prices; Homeownership; Life-cycle; Credit Conditions; Macro-prudential Policy